Exploración del entorno empresarial de Sevilla con un mapa de relación bidimensional - Tamayo Gallego, Juan Aurelio (Cuadernos de Estudios Empresariales, 2006)
In this paper we analyze the business environment of the province of Seville, showing a system of representation of inductive nature that adds individual opinions and at the same time sketches significant relations among the variables of the environment. For this purpose, after selecting consistent variables with the logic of Michael Porter’s complete system of the determinants of competitive advantage, we develop a relational map in the space of the two main components with the information obtained by interviewing managers and entrepreneurs of 80 business organizations in Seville. This diagram is the starting point for our discussion of possible connections among the variables of the pattern, making it feasible, along with other logical and theoretical arguments, to formulate and test a group of hypotheses about concepts such as innovation, quality, age and size of firms, cooperation, competition, concentration of sales, financing requirements and relations with the public administration.